Clinical Pharmacokinetics of Intra-arterial Melphalan and Topotecan Combination in Patients with Retinoblastoma - Taich, Paula Juliana (2014)
Purpose: To assess the antitumor activity, toxicity, and plasma pharmacokinetics of the combination of melphalan and topotecan for superselective ophthalmic artery infusion (SSOAI) treatment of children with retinoblastoma. Design: Single-center, prospective, clinical pharmacokinetic study. Participants: Twenty-six patients (27 eyes) with intraocular retinoblastoma. Methods: Patients with an indication for SSOAI received melphalan (3e6 mg) and topotecan (0.5e1 mg; doses calculated by age and weight). Plasma samples were obtained for pharmacokinetic studies, and a population approach via nonlinear mixed effects modeling was used. Safety and efficacy were assessed and compared with historical cohorts of patients treated with melphalan single-agent SSOAI. Main Outcome Measures: Melphalan and topotecan pharmacokinetic parameters and efficacy and safety parameters. Results: Twenty-seven eyes from 26 consecutive patients received 66 cycles of SSOAI melphalan and topotecan in combination. All 5 eyes treated as primary therapy responded to the combination chemotherapy and were preserved. Sixteen of the 22 eyes with relapsed or resistant tumors responded, but 3 of them ultimately underwent enucleation at a median of 8 months (range, 7.9e9.1 months). The incidence of grade III and IV neutropenia was 10.6% and 1.5%, respectively, which was comparable with historical controls of single-agent SSOAI melphalan. No episode of fever neutropenia was observed, and no patient required transfusion of blood products. The large variability in melphalan pharmacokinetics was explained by body weight (P<0.05). Concomitant topotecan administration did not influence melphalan pharmacokinetic parameters. There was no effect of the sequence of melphalan and topotecan administration in plasma pharmacokinetics. Conclusions: A regimen combining melphalan and topotecan for SSOAI treatment of retinoblastoma is active and well tolerated. This combination chemotherapy previously showed synergistic pharmacologic activity, and we herein provide evidence of not increasing the hematologic toxicity compared with single-agent melphalan.